Intravitreal bevacizumab as an adjunct in the management of a vascular choroidal granuloma - Bansal, Reema (BMJ Publishing Group, 2013)
A 43-year-old woman with tubercular choroidal granuloma showed poor response to conventional first-line four-drug antitubercular therapy (ATT) and corticosteroids. A therapeutic trial with intravitreal bevacizumab (1.25 mg in 0.05 mL) injections as an adjunct to ATT and corticosteroids led to a prompt initial regression of granuloma with restoration of visual acuity that was sustained for almost 2 years. A subsequent recurrence of the same lesion with evidence of enhanced vascularity was treated with intravitreal bevacizumab alone, that led to a complete regression of the granuloma with no recurrence until 1 year of follow-up.